Apples or candy? Internal and external influences on children's food choices. (1st October 2015) - Bruce, Amanda S.; Lim, Seung-Lark; Smith, Timothy Ryan; Cherry, J. Bradley C.; Black, William R.; Davis, Ann M.; Bruce, Jared M.
Highlights: Interoception and neural mechanisms exert a vital influence over food decisions. Early life feeding, peers, and food marketing also influence food choices. Examining these domains' intersection will advance our understanding of food choices. Abstract: The goal of this concise narrative review is to examine the current literature regarding endogenous and exogenous influences on youth food choices. Specifically, we discuss internal factors such as interoception (self-awareness) of pain and hunger, and neural mechanisms (neurofunctional aspects) of food motivation. We also explore external factors such as early life feeding experiences (including parenting), social influences (peers), and food marketing (advertising). We conclude with a discussion of the overlap of these realms and future directions for the field of pediatric food decision science.